STRATEGI PENGUATAN HAFALAN AL QUR’AN MELALUI KEGIATAN QUR’AN CAMP DI MTs MBS BARAT MAGETAN - Supriyadi, Nur; Happy Susanto; Lilis Sumaryanti (PT. Intelek Cendikiawan Nusantara, 2024)
In Indonesia, Islamic education There are two classified systems: the school system and the secondary system. In addition to religious education. In fact, Islamic boarding schools are traditional Islamic educational institutions in the form of mosques, holy places. (Khoiriyah, Susanto, and Abidin 2018). The community should consider madrasas from the perspective of their educational role, namely equipping students with competencies that the difference in religious atmosphere between madrasas and state schools is a factor that should make the community have a good perception of madrasas (Kanifah, Susanto, and Saputra 2020). preserving the Qur'an is by memorizing it. Therefore, MTs MBS Barat Magetan school must include a program to memorize and learn the Qur'an. The Quran Camp activity carried out at MTs MBS Barat Magetan is a strategy to inspire students to continue to memorize the Qur'an and pray in the hope of successfully achieving the goal of memorizing it. In this study, there are three objectives: (1) to find out how the Quran Camp is implemented in MBS MBS Barat Magetan, (2) to examine how to improve Quran memorization through Quran Camp activities in MBS MBS Barat Magetan, and (3) to assess the impact of Study Camp activities on strengthening Quran memorization. To find out the Quran camp activities that aim to improve Quran memorization in MTs MBS Barat Magetan. The researchers used a Qualitative research method so that this Collection uses interviews, observations, textual analysis as data collection methods. The findings of this study indicate that students' memorization reinforcement is very good.